Pemanfaatan Limbah Cucian Beras Hitam Sebagai Pupuk Organik Cair Terhadap Tanaman Sawi Hijau (Brassica juncea L) - murdaningsih murdaningsih; Josina Irene Brigetha Hutubessy; Albertus M.T Hurint (AGRICA, 2020)
This study aims to determine the application dose of liquid organic fertilizer from black rice wastewater on the growth and yield of mustard greens. The research was carried out at the Experimental Garden of the Faculty of Agriculture, the University of Flores for 6 months from June to November. The research was carried out using a randomized block design consisting of 6 doses of black rice liquid waste (Liquid Organic Fertilizer: LOF), namely: P0 = without LOF, P1 = 2,400 ltr/ha = 750 ml/plot; P2: 4800 ltr/ha = 1500 ml/plot; P3: 7200 ltr/ha = 2250 ml/plot; P4: 9600 ltr/ha = 3000 ml/plot; P5: 1200 ltr/ha = 3750 ml/plot; which was repeated 4 times, so there were 24 experimental experiments. The application of liquid organic fertilizer from black rice liquid waste to mustard greens showed an average response to an increase in plant height of 5.08%, leaf number of 7.95% and leaf area of 17.59%. The yield uptake variable was 11.51%, and the application dose of 9600 ltr/ha gave a plant height of 46.41 cm, a number of leaves 8.25, leaf area 1691.35 cm2, and fresh weight of mustard greens tan-1 of 153.65 and the weight of mustard ha-1 was 24.58 tonnes, but not significantly different from P3 (7200 ltr/ha).